2014
DOI: 10.1177/0021998314532151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fibre orientation and content on the mechanical, dynamic mechanical and thermal expansion properties of multi-layered glass/carbon fibre-reinforced polymer composites

Abstract: Ferrándiz Bou, S.; Balart Gimeno, RA. (2015). Effects of fibre orientation and content on the mechanical, dynamic mechanical and thermal expansion properties of multi-layered glass/carbon fibre-reinforced polymer composites. Journal of Composite Materials. 49(10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To investigate the viscoelastic behavior and structural properties of polymeric and metal matrix composite materials with the aim of determination their relevant damping and stiffness characteristics in our regular applications, dynamic mechanical analysis (DMA) was employed [7][8][9][10]. These dynamic properties obtained over a range of temperatures and frequencies are noteworthy, studies showed that the stacking sequence and fiber orientation influences the dynamic mechanical characteristics of hybrid polymeric composites [11][12][13][14][15]. Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the viscoelastic behavior and structural properties of polymeric and metal matrix composite materials with the aim of determination their relevant damping and stiffness characteristics in our regular applications, dynamic mechanical analysis (DMA) was employed [7][8][9][10]. These dynamic properties obtained over a range of temperatures and frequencies are noteworthy, studies showed that the stacking sequence and fiber orientation influences the dynamic mechanical characteristics of hybrid polymeric composites [11][12][13][14][15]. Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI.…”
Section: Introductionmentioning
confidence: 99%
“…As the properties of glass fibre having lower tensile modulus and higher failure to strain as compared to carbon fibre, glass fibre acts as improvement to the hybrid composite structure. The tensile properties such as tensile modulus in longitudinal/transverse direction, tensile strength in longitudinal/transverse direction, failure strain in longitudinal/transverse direction are more important to take into account together with cost saving [5]. The properties such as fibre content, orientation, dimension of constituent fibres (diameter), level of intermixing of fibres, interface bonding between fibre and matrix, and arrangement of fibres between different types of fibres, influences the mechanical properties of hybrid composite whereas the strength of hybrid composite relies on failure strains of each fibres where higher failure strain on one type of fibre could satisfy the others [4], [6].…”
Section: Figure 1 Positioning Of Classes Of Engineering Materials Showing the Advancement Of Composites [1]mentioning
confidence: 99%
“…Carbon fibre which possesses low elongation at break (approximately about 2%), leads to the brittle fracture of its composites. Hybridization from the use of two or more types of fibres reinforced the same resin, the disadvantages of one type fibres can be trade off by the advantages of the others [5]. It also provides synergetic increase of the failure strain of low elongation fibres when hybridised with higher elongation fibres.…”
Section: Figure 1 Positioning Of Classes Of Engineering Materials Showing the Advancement Of Composites [1]mentioning
confidence: 99%
“…However, a correction of the laying path would lead to a change in the fiber orientation. By changing the fiber orientation, forces can no longer be transmitted optimally, and it has an influence on the mechanical properties of the laminate [8].…”
Section: Introductionmentioning
confidence: 99%